ITO-SCADM Presentation Slides for Schema.org Crosswalk Presentation - Verhey, Chantelle (Zenodo, 2022)
The International Technology Office (ITO) gave a presentation to the Standing Committee on Antarctic Data Management (SCADM) in November 2020. The purpose of this presentation was to socialize the outputs from the Research Data Alliance - Research Metadata Schemas Working Group. These outputs include Schama.org crosswalks and the accompanying visualizations created by the ITO. Additionally the space was used to speak to data managers regarding community best practices, advantages, disadvantages and pathways towards semantic syndication. : World Data System - International Technology Office Funded under the Digital Research Alliance of Canada (formerly the Canadian New Digital Research Infrastructure Organization - NDRIO) collaborative agreement number 51387-50326.